Systematic review of observational studies assessing bleeding risk in patients with atrial fibrillation not using anticoagulants. - Luciane Cruz Lopes; Frederick A Spencer; Ignacio Neumann; Matthew Ventresca; Shanil Ebrahim; Qi Zhou; Neera Bhatnagar; Sam Schulman; John Eikelboom; Gordon Guyatt (PLoS ONE, 2014)
Background Patients with atrial fibrillation considering use of anticoagulants must balance stroke reduction against bleeding risk. Knowledge of bleeding risk without the use of anticoagulants may help inform this decision. Purpose To determine the rate of major bleeding reported in observational studies of atrial fibrillation patients not receiving Vitamin K antagonists (VKA). Data sources We searched MEDLINE, EMBASE and CINAHL to October 2011 and examined reference lists of eligible studies and related reviews. Study selection All longitudinal cohort studies that included over 100 adult patients with atrial fibrillation not receiving VKA. Data extraction Teams of two reviewers independently and in duplicate adjudicated eligibility, assessed risk of bias and abstracted study characteristics and outcomes. Data synthesis Twenty-one eligible studies included 96,448 patients. Major bleeding rates varied widely, from 0 to 4.69 events per 100 patient-years. The pooled estimate in 13 studies with 78839 patients was 1.59 with a 99% confidence interval of 1.10 to 2.3 and median 1.42 (interquartile range 0.62-2.70). Pooled estimates for fatal bleeding and non-fatal bleeding from 4 studies that reported these outcomes were, respectively, 0.40 (0.34 to 0.46) and 1.18 (0.30 to 4.56) per 100 patient-years. In 9 randomized controlled trials (RCTs) the median rate of major bleeding in patients not receiving either anticoagulant or antiplatelet therapy was 0.6 (interquartile 0.2 to 0.90), and in 12 RCTs the median rate of major bleeding in patients receiving a single antiplatelet agent was 0.75 (interquartile 0.4 to 1.4). Conclusion Results suggest that patients with atrial fibrillation not receiving VKA enrolled in observational studies represent a population on average at higher risk of bleeding.